Design and Synthesis of a Focused Library of Diamino Triazines as Potential Mycobacterium tuberculosis DHFR Inhibitors - Lele, Arundhati C. (ACS Med Chem Lett, 2015)
[Image: see text] We report design of a series of 2,4-diamino triazines as Mycobacterium tuberculosis (Mtb) dihydrofolate reductase inhibitors. The synthesized compounds were evaluated against Mtb (H(37)Rv and Dormant stage H(37)Ra), their cytotoxicity was assessed (HepG2 and A549 cell lines), and selectivity toward Mtb was evaluated by testing against other bacterial strains. Some derivatives showed promising activity along with low cytotoxicity. The most potent compound in the whole cell assay (MIC 0.325 μM against H(37)Rv) showed selectivity in the enzyme assay and exhibited synergy with second line anti-TB agent p-amino salicylic acid. This study therefore provides promising molecules for further development as antituberculosis DHFR inhibitors.